Factors Influencing Students’ Motivation to Use ChatGPT for Learning: A TAM and UGT Approach - Azizah, Istighfarin Rochmatul; Nugraha, Jaka (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2025)
This study investigates the factors influencing university students’ motivation to use ChatGPT for learning, addressing a research gap in understanding how students perceive and adopt generative AI tools in academic contexts. Despite ChatGPT’s growing presence in higher education and its potential to support autonomous and flexible learning, limited empirical research has examined the motivational factors driving its use. Specifically, the study evaluates the impact of four key variables—perceived ease of use, perceived usefulness, information seeking, and novelty—on students’ intention to use ChatGPT for learning activities. The research was conducted among 274 students from the Office Administration Education Study Program at Universitas Negeri Surabaya, selected through purposive sampling. Employing a quantitative approach, data were collected via a structured survey and analyzed using Structural Equation Modeling–Generalized Structured Component Analysis (SEM–GSCA). The findings reveal that all four variables exert a positive and significant influence on students’ intention to use ChatGPT, providing empirical support for both the Technology Acceptance Model (TAM) and Uses and Gratifications Theory (UGT). The study concludes that students’ perceptions of ChatGPT’s ease of use, usefulness, novelty, and ability to fulfill information needs are critical drivers of their motivation to integrate the tool into their learning practices. Theoretical implications include advancing research on AI adoption in education, while practical implications encourage educators and institutions to promote responsible and effective use of AI tools like ChatGPT to support self-directed and adaptive learning. This study also provides insights into how generative AI influences students’ long-term learning motivation and behavioral intentions.